Dietary administration of the glycolytic inhibitor 2-deoxy-D-glucose reduces endotoxemia-induced inflammation and oxidative stress: Implications in PAMP-associated acute and chronic pathology - Pandey, Sanjay; Anang, Vandana; Singh, Saurabh; Seth, Saurabh; Bhatt, Anant Narayan; Kalra, Namita; Manda, Kailash; Soni, Ravi; Roy, Bal Gangadhar; Natarajan, K.; Dwarakanath, Bilikere S. (Frontiers in Pharmacology, 2023)
Pathogen associated molecular patterns (PAMPs) like bacterial cell wall components and viral nucleic acids are known ligands of innate inflammatory receptors that trigger multiple inflammatory pathways that may result in acute inflammation and oxidative stress driven tissue and organ toxicity. When dysregulated, this inflammation may lead to acute toxicity and multiorgan failure. Inflammatory events are often driven by high energy demands and macromolecular biosynthesis. Therefore, we proposed that targeting the metabolism of lipopolysaccharide (LPS) driven inflammatory events, using an energy restriction approach, can be an effective strategy to prevent the acute or chronic detrimental effects of accidental or seasonal bacterial and other pathogenic exposures. In the present study, we investigated the potential of energy restriction mimetic agent (ERMA) 2-deoxy-D-Glucose (2-DG) in targeting the metabolism of inflammatory events during LPS elicited acute inflammatory response. Mice fed with 2-DG as a dietary component in drinking water showed reduced LPS driven inflammatory processes. Dietary 2-DG reduced the LPS induced lung endothelial damage and oxidative stress by strengthening the antioxidant defense system and limiting the activation and expression of inflammatory proteins viz. P-Stat-3, Nf and MAP kinases. This was accompanied by decreased TNF, IL-1β and IL-6 levels in peripheral blood and bronchoalveolar lavage fluid (BALF). 2-DG also reduced the infiltration of PMNCs in the inflamed tissues. Altered glycolysis and improved mitochondrial activity in 2-DG treated RAW264.7 macrophage cells suggested the possible impairment of macrophage metabolism and therefore activation in macrophages. Taken together, the present study suggests that inclusion of glycolytic inhibitor 2-DG as a part of the diet can be helpful in preventing severity and poor prognosis associated with the inflammatory events during bacterial and other pathogenic exposures.